The unfinished business of regionalism and tradition in Portuguese modern architecture - Agarez, R. C. (Arkkitehti Finnish Architectural Review, 2021)
To turn the witchcraft against the wizard, which is much more useful than creating one’s own witchcrafts.” This was how Victor Palla, a Lisbon-based architect, described in 1949 his (post-war) generation’s strategy to address concerns with built environment traditions in conservative, dictatorship-led Portugal: tradition’s strength should be acknowledged, and competent designers would “derive from it a means of defence for modern architecture”. Such was the actual importance of tradition.